the, to, the, and, of, on, a The Legal Approach to the Sale and Purchase of Goods on Board: a Comparative Legal Study - Ade Fisti Pongoliu; Ahmadi Miru; Iin Karita Sakharina (Hang Tuah Law Journal, 2020)
This study aims to analyze and understand the legal protection of parties involved in the sale and purchase of goods on board. This research is normative legal research using statutory, conceptual, and comparative approaches. The results showed that legal protection for parties in the sale and purchase of goods on board included legal protection for PT. Garuda Indonesia, PT. Rodamas and legal protection for passengers. PT. Rodamas provided compensation to PT. Garuda Indonesia after PT. Garuda Indonesia has provided compensation to passengers in case of loss. Also, PT. Garuda Indonesia is personally responsible for any loss caused by the company's fault or negligence. The legal arrangement of sale and purchase in the CISG Convention does not apply to the sale and purchase of personal goods between PT. Garuda Indonesia and passengers, because CISG regulates sale and purchase of goods agreements between different countries' business actors.